Can power be made an empirically viable concept in policy process theory? Exploring the power potential of the Narrative Policy Framework - Tjorven Sievers; Michael D. Jones (International Review of Public Policy)
Despite the range of analytical foci in current policy process theory, the idea of an empirically sound power concept has not received much attention. While scientifically oriented process frameworks tend to be either implicitly or explicitly based on a pluralist understanding of power, critical theory focused approaches frequently point to power inequality in the policy process but remain vague on its conceptualization. As a result, the concept of power remains underspecified, which renders theoretical understanding of policy-making incomplete. In this article, we argue that it is necessary to integrate an empirically viable power concept into policy process theory which allows researchers to systematically assess the role of structural power imbalances in policymaking, without compromising scientific rigor. To that end, we examine how power has been treated in policy process theory, with focus on the Advocacy Policy Framework (ACF), Social Construction and Policy Design, and—primarily—the Narrative Policy Framework (NPF). In a second step, we explore how Steven Lukes’ three-dimensional power concept can be leveraged by the NPF to bridge the gap between different understandings of power, while also articulating a concept of power amenable to scientific testing within policy studies.